2017
DOI: 10.1007/s00259-017-3814-1
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of multiple organ amyloid involvement in systemic amyloidosis using 11C-PiB PET imaging

Abstract: C-PiB PET imaging can be used clinically in the systemic evaluation of amyloid distribution in patients with AL and ATTRm amyloidosis. Quantitative analysis of C-PiB PET images may be useful in therapy evaluation and will reveal whether amyloid clearance is correlated with clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 34 publications
0
48
0
1
Order By: Relevance
“…In humans, most of the CSF drains into the blood via arachnoid villi and granulations in the major venous sinus [70]. In recent years, studies have found that CSF can drain solutes, such as Aβ, out of the brain through the glymphatic system, along cranial nerves and possible lymphatic vessels in the dura [71][72][73][74]. In line with these findings, single-photon emission computed tomography combined with a systemic injection of radiolabeled Pittsburg Compound B (PiB) in rodents demonstrated that Aβ is drained out of the brain through the ISF/CSF in the nasal mucosa [75].…”
Section: Isf Bulk Flow and Perivascular Aβ Clearancementioning
confidence: 99%
“…In humans, most of the CSF drains into the blood via arachnoid villi and granulations in the major venous sinus [70]. In recent years, studies have found that CSF can drain solutes, such as Aβ, out of the brain through the glymphatic system, along cranial nerves and possible lymphatic vessels in the dura [71][72][73][74]. In line with these findings, single-photon emission computed tomography combined with a systemic injection of radiolabeled Pittsburg Compound B (PiB) in rodents demonstrated that Aβ is drained out of the brain through the ISF/CSF in the nasal mucosa [75].…”
Section: Isf Bulk Flow and Perivascular Aβ Clearancementioning
confidence: 99%
“…In several organ systems, including kidney (13% vs. 28%) and abdominal wall fat (10% vs. 13%), PET identified involvement in fewer subjects than did international consensus. Quantitative analysis of 18 F-florbetapir PET/CT revealed more frequent organ involvement than did visual analysis in the tongue, thyroid, lung, pancreas, kidney, muscle, and humeral head. Extensive organ amyloid deposits were observed in active AL as well as in AL remission cohorts, and in both cardiac and noncardiac AL cohorts.…”
mentioning
confidence: 78%
“…An SUV max of at least 2.5 was considered abnormal in all organs other than the liver. Results: Compared with the international consensus definition of organ involvement, 18 F-florbetapir PET/CT identified amyloid deposits in substantially higher percentages of subjects for several organ systems, including parotid gland (50% vs. 3%), tongue (53% vs. 10%), and lung (35% vs. 10%). In several organ systems, including kidney (13% vs. 28%) and abdominal wall fat (10% vs. 13%), PET identified involvement in fewer subjects than did international consensus.…”
mentioning
confidence: 94%
See 2 more Smart Citations